Effect of moisture on electrical response of sand and clay under high impulse voltage applications - Siow, Chun Lim; Johari, Mohd Syariffuddin; Gomes, Chandima (Universiti Putra Malaysia Press, 2017)
Soil plays an important role in ground designing. Engineers normally consider only soil resistivity under normal or steady state condition when designing the grounding system. Under certain circumstances such as lightning, electrical response of the soil will change accordingly and thus, the performance of the grounding system will be affected. The purpose of this study is to investigate the effect of moisture content on the electrical behaviour of sand and clay under high impulse voltage condition. Both soil samples are dried in the oven at 110 Â± 5°C to remove the water content until became 0%. The samples are subjected to 30 shots of standard (1.2/50Âµs) lightning impulse voltage for both positive and negative impulse polarities. This is followed by moistening the samples with 5% amount of water over the volume of the samples. The corresponding V50% for both sand and clay was calculated and the value obtained was converted to standard atmospheric condition. The voltage at breakdown and time to breakdown for each soil sample was analysed a statistical analysis conducted for these two parameters to determine if type of soil and moisture content have an effect on the breakdown voltage. In general, it was found that clay is more efficient in neutralising high impulse voltage than sand likely due to the former's low resistivity and porosity.